2021
DOI: 10.18632/aging.202662
|View full text |Cite
|
Sign up to set email alerts
|

Platelets transport β-amyloid from the peripheral blood into the brain by destroying the blood-brain barrier to accelerate the process of Alzheimer's disease in mouse models

Abstract: Extracellular aggregation of the β-amyloid (Aβ) peptide into toxic multimers in the brain is a prominent event occurring in the pathogenesis of Alzheimer’s disease (AD), and a large amount of Aβ in the blood is derived from platelets. Thus, we speculated that platelets may play an important role in the process of AD. We first investigated the changes in platelet Aβ secretion with age. Then, we injected platelets from aged amyloid precursor protein APP/PS1 mice into young C57 mice and assessed their memory capa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 47 publications
0
23
0
Order By: Relevance
“…To support this hypothesis, it was shown that Aβ undergoes daily oscillation in interstitial fluid in the vicinity of brain blood vessels, suggesting a possible influx of Aβ from the periphery into CNS (Kress et al, 2018 ). Very recent studies indicate that platelets can contribute to BBB disruption (Kopeikina et al, 2020 ; Wu et al, 2021 ) and can transfer Aβ from blood vessels into CNS (Wu et al, 2021 ; Table 1 ). Moreover, it was demonstrated that activated platelets from APP/PS1 transgenic mice invade brain parenchyma and are closely associated with astrocytes (Kniewallner et al, 2020 ) that are enriched with major brain gangliosides in lipid rafts of astroglial limitations and efficiently activate platelets (Sotnikov et al, 2013 ).…”
Section: Alzheimer’s Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…To support this hypothesis, it was shown that Aβ undergoes daily oscillation in interstitial fluid in the vicinity of brain blood vessels, suggesting a possible influx of Aβ from the periphery into CNS (Kress et al, 2018 ). Very recent studies indicate that platelets can contribute to BBB disruption (Kopeikina et al, 2020 ; Wu et al, 2021 ) and can transfer Aβ from blood vessels into CNS (Wu et al, 2021 ; Table 1 ). Moreover, it was demonstrated that activated platelets from APP/PS1 transgenic mice invade brain parenchyma and are closely associated with astrocytes (Kniewallner et al, 2020 ) that are enriched with major brain gangliosides in lipid rafts of astroglial limitations and efficiently activate platelets (Sotnikov et al, 2013 ).…”
Section: Alzheimer’s Diseasementioning
confidence: 99%
“…Using the parabiosis model, where there was connected the blood system of control (wild-type, WT) mice and transgenic mice with human APP overexpression in the CNS, it was revealed that in a previously healthy WT mouse the brain exhibited signs of AD that include Aβ depositions, neurodegeneration, and neuroinflammation (Bu et al, 2018 ). Thus, platelets can secrete various processed forms of APP and other substances while infiltrating the brain, which results in the growth of Aβ depositions in the brain and increases the permeability of BBB (Espinosa-Parrilla et al, 2019 ; Wu et al, 2021 ). We demonstrated that major brain gangliosides within neuronal lipid rafts in post-synaptic membranes induced platelets’ granule release (Sotnikov et al, 2013 ) suggesting a possible mechanism of Aβ secretion by platelets in the CNS.…”
Section: Alzheimer’s Diseasementioning
confidence: 99%
“…There is evidence showing that activated platelets may contribute to the formation of cerebral amyloid angiopathy 63,64 and Aβ deposition in the brain parenchyma. 65 Moreover, in AD patients, increased platelet activation has been observed, 66 which, together with the above evidence, indicates that platelets-derived Aβ may contribute to the development of AD. In future, more evidence needs to be accumulated to deeply elucidate the roles of platelets-derived Aβ in the pathogenesis of AD.…”
Section: Introductionmentioning
confidence: 89%
“…The efficiency of platelet depletion in the brain was similar between females and males, with platelet-depleted mice showing about 97% lower platelet numbers in the brain compared with sex-matched IgG treated mice (hippocampus: females: IgG = 920.3 ± 528.9 platelets/mm 3 versus αCD42b = 26.6 ± 10.88 platelets/mm 3 ; males: IgG = 563.4 ± 473.8 platelets/mm 3 versus αCD42b = 16.67 ± 5.51 platelets/mm 3 ). Platelets are one of the major sources of blood circulating amyloid beta [21,22], and platelet-derived amyloid beta seems to be involved in the formation of cerebrovascular [24,26] and cerebral amyloid beta deposits [25]. Thus, we first investigated whether platelet depletion changed amyloid plaque pathology in APP-PS1 mice.…”
Section: Anti-cd42b Antibody Injection Induces Platelet Depletion In ...mentioning
confidence: 99%
“…They express APP and produce amyloid beta peptides [16,17], which are secreted upon platelet activation [17]. In AD, platelets have an increased activation status [23] and might contribute to cerebrovascular and cerebral amyloid beta deposition [24][25][26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%